Mycoflora of Stored Wheat in Bafra District of Samsun Province - Kansu, Bayram; Tunali, Berna; Eser, Ümit (My University, 2024)
In this study, the fungal flora in wheat grain samples taken six months after harvest from warehouses in 13 villages of Bafra district of Samsun province was investigated. A total of 600 seeds were processed isolates of endophytic, saprophytic, or pathogenic fungi recovered were identified as 15 fungal genera. Alternaria alternata, Alternaria spp., Chaetomium spp., Phoma spp., Epicoccum nigrum were the fungi that showed the highest colonization frequency in analyzed grain. Fungi such as Penicillium, Aspergillus, Fusarium graminearum, F. poae, which are known to produce mycotoxins, were among the isolated fungi. Fusarium graminearum, F. poae and Bipolaris sorokiniana are among the important pathogens of wheat. The other microorganisms were present at intermediate or low values. On the other hand, fungi such as Chaetomium, Epicoccum nigrum, Torula species were isolated as antagonist organisms. Stemphylum, Ulocladium, Cladosporium, Popularia, Nigrospora oryzae, which are thought to be saprophytes or endophytes, were also isolated. Some are also known as weak pathogens. On average, 31.5% of the seeds examined had one or more fungal infections, while 68.5% had no fungal infections.